“É possível aprender inglês tendo aula duas vezes por semana?”: um estudo bibliográfico sobre competências e estratégias do aprendiz de línguas - Almeida, Elom de Paulo Andrade de (Universidade Federal de São Carlos, 2021)
Studies on the communicative approach in the area of language teaching and learning (HYMES, 1972; ALMEIDA FILHO, 1993) redefined the role of teachers and students, characterizing the latter as a protagonist in the learning process, and the former as a facilitator and mediator of this process. However, the awareness of students about their role and the way they should monitor their learning, in many cases, still need to be developed (RIBEIRO, 2009). Based on these considerations, this research proposes theoretical approaches to the following question: “Is it possible to learn English by taking classes twice a week?”, asked by a student in a real class context. This questioning led us to two inferences: (i) the possible dependence of the student on the school environment and (ii) the possibility that the student does not consider learning in extra-class contexts as part of her learning process. In order to understand and discuss these conjectures, we base this research on studies of Language Learners' Competences (CUNHA, 2008; DE PAULA, 2008; RIBEIRO, 2009; NASCIMENTO, 2009; ALMEIDA FILHO, 2014) and Learning Strategies (RUBIN, 1975; WENDEN, 1991; OXFORD, 1990; COHEN, 1998), carrying out a brief review of both concepts, to then analyze and reflect on possible interrelations, associations and contrasts that could help answer the initial question. Through this bibliographic research, with a qualitative basis, it was possible to infer that the study of the learner's competences, in addition to the aim of enabling the students to develop awareness of their responsibility in relation to their own learning, also corroborates the importance of the school context in the development of social aspects related to the role of the students, so that they have contact with an adequate theory presented by the teacher. Learning strategies, in turn, besides serving as a relevant theory, allow the materialization of the learner's competences through productive practices, contributing to promote the development of learning in different contexts.
“Is it possible to learn English by taking classes twice a week?”: a bibliographic study about competences and strategies of language learners
Keywords: Linguística aplicada; Aprendizagem de línguas; Competências de aprender; Estratégias de aprendizagem; Applied Linguistics; Language learning; Learning competences; Learning strategies; LINGUISTICA, LETRAS E ARTES::LINGUISTICA::LINGUISTICA APLICADA